The impact of different cone beam computed tomography and multi-slice computed tomography scan parameters on virtual three-dimensional model accuracy using a highly precise ex vivo evaluation method. Issue 5 (May 2016) - Matta, Ragai-Edward; von Wilmowsky, Cornelius; Neuhuber, Winfried; Lell, Michael; Neukam, Friedrich W.; Adler, Werner; Wichmann, Manfred; Bergauer, Bastian
Abstract: Objectives: Multi-slice computed tomography (MSCT) and cone beam computed tomography (CBCT) are indispensable imaging techniques in advanced medicine. The possibility of creating virtual and corporal three-dimensional (3D) models enables detailed planning in craniofacial and oral surgery. The objective of this study was to evaluate the impact of different scan protocols for CBCT and MSCT on virtual 3D model accuracy using a software-based evaluation method that excludes human measurement errors. Material and methods: MSCT and CBCT scans with different manufacturers' predefined scan protocols were obtained from a human lower jaw and were superimposed with a master model generated by an optical scan of an industrial noncontact scanner. To determine the accuracy, the mean and standard deviations were calculated, and t-tests were used for comparisons between the different settings. Results: Averaged over 10 repeated X-ray scans per method and 19 measurement points per scan (n = 190), it was found that the MSCT scan protocol 140 kV delivered the most accurate virtual 3D model, with a mean deviation of 0.106 mm compared to the master model. Only the CBCT scans with 0.2-voxel resolution delivered a similar accurate 3D model (mean deviation 0.119 mm). Conclusion: Within the limitations of this study, it was demonstrated that the accuracy of a 3D model of the lower jaw depends on the protocol used for MSCT and CBCT scans.